Analisis Aspek Lokalitas Mahmud Yunus dalam Tafsir Al-Qur'an Al-Karim - Muhammad Khai Hanif Yuli Edi Z; Halimatussadiyah Halimatussadiyah; Zulkipli Jemain (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2023)
This article analyzes the aspects of locality in Mahmud Yunus' interpretation of the Noble Qur'an, Al-Karim. The interpretation has undergone 23 reprints and is recognized as an important work in the interpretation of the Qur'an in Indonesia. The study employs a historical-intertextual approach to explore the background of Mahmud Yunus' life, his social context, and the influence of his thoughts in the interpretation. Descriptive analysis is used to depict the local elements present in the interpretation. The analysis reveals three main aspects of locality in Mahmud Yunus' interpretation of the Noble Qur'an, Al-Karim. Firstly, there is locality in terms of language, with the use of local expressions such as